2012
DOI: 10.1007/s00122-012-1907-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of adult-plant resistance to stripe rust in a population derived from common wheat cultivars Naxos and Shanghai 3/Catbird

Abstract: Stripe rust, caused by Puccinia striiformis Westend. f. sp. tritici Erikss., is a severe foliar disease of common wheat (Triticum aestivum L.) worldwide. Use of adult-plant resistance (APR) is an efficient approach to provide long-term protection of crops from the disease. The German spring wheat cultivar Naxos showed a high level of APR to stripe rust in the field. To identify the APR genes in this cultivar, a mapping population of 166 recombinant inbred lines (RILs) was developed from a cross between Naxos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 69 publications
6
61
0
Order By: Relevance
“…1_GWAS , respectively), which were mapped in close proximity to the IWA7306 locus. Similarly, Zwart et al [45] and Ren et al [44] reported two QTL, QYr . sun-7A_CPI133872 and QYr .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…1_GWAS , respectively), which were mapped in close proximity to the IWA7306 locus. Similarly, Zwart et al [45] and Ren et al [44] reported two QTL, QYr . sun-7A_CPI133872 and QYr .…”
Section: Discussionmentioning
confidence: 83%
“…caas-1BL . 1RS_SHA3/CBRD , was also mapped close to the region of IWA1191 (4.6–6.3 cM) [44], which could be related to IWA1191 .…”
Section: Discussionmentioning
confidence: 99%
“…1. Chromosome 1A had four QTLs described (Bariana et al 2010; Dedryver et al 2009; Ren et al 2012a; Rosewarne et al 2012). The flanking markers of these form two distinct groups although they are both on the long arm of chromosome 1A.…”
Section: Groupmentioning
confidence: 99%
“…There were three QTLs identified on Chromosome 1DS (Ren et al 2012a; Vazquez et al 2012, Zwart et al 2010), all with relatively minor and inconsistent effects against the pathogen. These loci probably form two separate regions with the Stephens (Vazquez et al 2012) and CPI133872 (Zwart et al 2010) QTLs being in the telomeric region of 1DS.…”
Section: Groupmentioning
confidence: 99%
“…Five QTLs, QYr. jirc-6B (Suenaga et al 2003), QYr.inra-6B (Dedryver et al 2009), QYr.caas-6BS (Lan et al 2010), QYr.caas-6BS.2 (Ren, Y et al 2012a), and QYr.caas-6BS.3 (Ren, Y et al 2012b) explained phenotypic variation less than 10 %. These QTLs explained part of the phenotypic variance, but YrLM168a confers complete resistance as a single gene.…”
Section: Discussionmentioning
confidence: 96%